The role of decorative rocks in the historiographical evolution of the Hispanic Early Middle Ages - Aranda González, Raúl (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The study of the exploitation, distribution, uses and meanings of decorative rocks in the early Middle Ages has become a major topic in the historiographical scene in recent years. In order to provide an in-depth reflection on the issue, a compilation of the history of research on the subject is presented. It analyses the contribution to knowledge about the phenomenon of decorative lapidary material from the art-historical literatura of Romanticism to current postulates.
Keywords: decorative rocks; marmor; Early Middle Ages; Early Medieval architecture